1998
DOI: 10.1182/blood.v91.7.2565
|View full text |Cite
|
Sign up to set email alerts
|

Response of Monocyte Iron Regulatory Protein Activity to Inflammation: Abnormal Behavior in Genetic Hemochromatosis

Abstract: In genetic hemochromatosis (GH), iron overload affects mainly parenchymal cells, whereas little iron is found in reticuloendothelial (RE) cells. We previously found that RE cells from GH patients had an inappropriately high activity of iron regulatory protein (IRP), the key regulator of intracellular iron homeostasis. Elevated IRP should reflect a reduction of the iron pool, possibly because of a failure to retain iron. A defect in iron handling by RE cells that results in a lack of feedback regulation of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The host defence directed against intracellular pathogens such as Salmonellae strongly depends on IFN-gdriven macrophage immune effector pathways which are regulated by the intraphagocyte iron content. While a minimum amount of iron is required for the generation of toxic oxygen species by phox (Collins et al, 2002), macrophage iron overload inhibits the transcription of iNOS and thus the generation of NO (Weiss et al, 1994;Dlaska and Weiss, 1999), the formation of TNF-a and antigen presentation via MHC II (Recalcati et al, 1998;Oexle et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host defence directed against intracellular pathogens such as Salmonellae strongly depends on IFN-gdriven macrophage immune effector pathways which are regulated by the intraphagocyte iron content. While a minimum amount of iron is required for the generation of toxic oxygen species by phox (Collins et al, 2002), macrophage iron overload inhibits the transcription of iNOS and thus the generation of NO (Weiss et al, 1994;Dlaska and Weiss, 1999), the formation of TNF-a and antigen presentation via MHC II (Recalcati et al, 1998;Oexle et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Iron is a critical determinant in host-pathogen interplay because it affects cell-mediated immune pathways while also representing an essential nutrient for microbes (Weinberg, 1992;Weiss, 2002). Iron exerts an inhibitory effect towards interferon-g (IFN-g) activity, which negatively affects antimicrobial effector pathways of macrophages including the expression of inducible nitric oxide synthase (iNOS) and of tumour necrosis factor-a (TNF-a) (Weiss et al, 1994;Recalcati et al, 1998;Oexle et al, 2003). Importantly, the expression of iron acquisition systems by pathogens has been linked to their pathogenicity and is essential for microbial growth and proliferation (Boyer et al, 2002;Schrettl et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to most other types of cells where hereditary hemochromatosis leads to Fe overload, reticuloendothelial macrophages and monocytes from individuals with hereditary hemochromatosis exhibit decreased intracellular Fe levels due to excessive Fe efflux relative to cells from healthy control subjects [22][23][24][25]. In previous work, we demonstrated that M.tb cultured in monocyte-derived macrophages (MDM) from individuals with hereditary hemochromatosis acquire significantly less Fe from Tf than MDM from normal subjects [26].…”
Section: Introductionmentioning
confidence: 90%
“…Our previous studies have shown that M.tb residing within MDM from subjects with hemochromatosis acquire less Fe from Tf than bacilli located in MDM from healthy control subjects [26]. This could be related to alterations in TfR function or to the decrease in the labile pool of Fe in the macrophage cytoplasm that has been shown to occur in these cells [22][23][24][25]. To address these two possibilities, we examined whether there is a difference in Fe acquisition from Lf, by intraphagosmal M.tb residing within MDM derived from individuals with hereditary hemochromatosis relative to those from healthy control subjects.…”
Section: Mtb Residing Within Macrophages From Hemochromatosis Patienmentioning
confidence: 96%
See 1 more Smart Citation